The Study of Sinbad’s Personality Change in Magi: Adventure Of Sinbad and Magi: Labyrinth Of Magic Manga Series - Celine Alexandra Maria Utomo (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This thesis focuses on the journey of Sinbad, the main character of Magi: Adventure of Sinbad and Magi: Labyrinth of Magic Manga series. These manga series present the adventure of an ordinary young boy named Sinbad who will go through several stages in his journey in order to become a hero. The result of undergoing those stages will affect Sinbad’s personality change process. Because of this, I am interested in analyzing the process of Sinbad’s personality change in his journey to become a hero. I use the monomyth theory to analyze the process of Sinbad’s journey, and the theory of personality development to analyze Sinbad’s personality change throughout his journey. First, I am going to analyze Sinbad’s personality before he embarks on his journey, second, I am going to analyze the process of his personality change, and lastly, I discuss Sinbad’s personality after his journey. Keywords: Journey, Personality Change, Hero